Epigenetic Profiling and Response to CD19 Chimeric Antigen Receptor T-Cell Therapy in B-Cell Malignancies. (28th September 2021) - Garcia-Prieto, Carlos A; Villanueva, Lorea; Bueno-Costa, Alberto; Davalos, Veronica; González-Navarro, Europa Azucena; Juan, Manel; Urbano-Ispizua, Álvaro; Delgado, Julio; Ortiz-Maldonado, Valentín; del Bufalo, Francesca; Locatelli, Franco; Quintarelli, Concetta; et al.
Abstract: Background: Chimeric antigen receptor (CAR) T cells directed against CD19 (CART19) are effective in B-cell malignancies, but little is known about the molecular factors predicting clinical outcome of CART19 therapy. The increasingly recognized relevance of epigenetic changes in cancer immunology prompted us to determine the impact of the DNA methylation profiles of CART19 cells on the clinical course. Methods: We recruited 114 patients with B-cell malignancies, comprising 77 patients with acute lymphoblastic leukemia and 37 patients with non-Hodgkin lymphoma who were treated with CART19 cells. Using a comprehensive DNA methylation microarray, we determined the epigenomic changes that occur in the patient T cells upon transduction of the CAR vector. The effects of the identified DNA methylation sites on clinical response, cytokine release syndrome, immune effector cell-associated neurotoxicity syndrome, event-free survival, and overall survival were assessed. All statistical tests were 2-sided. Results: We identified 984 genomic sites with differential DNA methylation between CAR-untransduced and CAR-transduced T cells before infusion into the patient. Eighteen of these distinct epigenetic loci were associated with complete response (CR), adjusting by multiple testing. Using the sites linked to CR, an epigenetic signature, referred to hereafter as the EPICART signature, was established in the initial discovery cohort (n = 79), which was associated with CR (Fisher exact test, P < .001) and enhanced event-free survival (hazard ratio [HR] = 0.36; 95% confidence interval [CI] = 0.19 to 0.70; P = .002; log-rank P = .003) and overall survival (HR = 0.45; 95% CI = 0.20 to 0.99; P = .047; log-rank P = .04;). Most important, the EPICART profile maintained its clinical course predictive value in the validation cohort (n = 35), where it was associated with CR (Fisher exact test, P < .001) and enhanced overall survival (HR = 0.31; 95% CI = 0.11 to 0.84; P = .02; log-rank P = .02). Conclusions: We show that the DNA methylation landscape of patient CART19 cells influences the efficacy of the cellular immunotherapy treatment in patients with B-cell malignancy.